Association Between Dietary Iron Intake and Serum Ferritin and Severe Headache or Migraine - Meng, Shu-Han; Zhou, Hai-Bo; Li, Xin; Wang, Ming-Xue; Kang, Li-Xin; Fu, Jin-Ming; Li, Xia; Li, Xue-Ting; Zhao, Ya-Shuang (Frontiers in Nutrition, 2021)
Background: Dietary iron intake and serum ferritin in relation to severe headache or migraine remain largely unknown. So we investigated the association between dietary iron intake and serum ferritin and severe headache or migraine among American adults. Methods: This cross-sectional study included 7880 adults (≥ 20 years) from the National Health and Nutrition Examination Surveys (NHANES) of America from 1999 to 2004. We performed multivariable logistic regression and restricted cubic spline (RCS) regression to assess the association of dietary iron and serum ferritin with severe headache or migraine. Results: Among women aged 20-50 years, the adjusted OR of the association between dietary iron intake and migraine for comparing the highest quintile of dietary iron intake (≥ 17.48 mg/day) with the lowest quintile of dietary iron intake (≤ 7.77 mg/day) was 0.571 (0.398, 0.819). The adjusted OR of the association between serum ferritin and migraine was 0.492 (0.332, 0.730) comparing the highest quintile of serum ferritin (≥ 161 ug/L) with the lowest quintile of serum ferritin (≤ 34 ug/L) among women aged over 50 years. For men, there was no statistically significant relationship between dietary iron and serum ferritin and severe headache or migraine. Conclusions: Most women aged 20-50 years consumed less dietary iron than their recommended dietary allowances. Dietary iron intake was inversely associated with severe headache or migraine in women aged 20-50 years. For women over 50 years, serum ferritin level was negatively associated with severe headache or migraine.